ANALISIS INTENSITAS KEBISINGAN TERHADAP KELELAHA KERJA OPERATOR PRODUKSI DI PT EOB - Purba, Jentry Octavianus; Zetli, Sri (LPPM Universitas Putera Batam, 2021)
ABSTRACT The goal of this research was to look at the intensity of machines and equipment in areas one and two of production, as well as the impact of machines and equipment on job weariness at PT EOB. Area one has the maximum intensity of production created by machinery and equipment at 109 dBA, whereas area two has the highest intensity at 103 dBA. A production questionnaire was sent to all operators in the sampled region in addition to utilizing tools to estimate the noise level received. The job tiredness level instrument, on the other hand, has an average score of 27.15, with a proportion of weariness of 75%. The value of r = 0.794, as determined by statistical tests utilizing Person Correlation, indicates that there is a reasonably strong correlation and close association where the value of r is in the range of 0.61-0.80. This indicates that the more work tiredness there is, the more work fatigue there is. The test yielded a 0.05 probability significance. As a result, it may be argued that H0 is rejected and H1 is accepted, implying that noise has an influence on job weariness.